Biomass-derived CO2 rich syngas conversion to higher hydrocarbon via Fischer-Tropsch process over Fe–Co bimetallic catalyst. (22nd October 2019) - Sonal,; Ahmad, Ejaz; Upadhyayula, Sreedevi; Pant, Kamal K.
Abstract: Biomass-derived syngas (CO2 + CO + H2 ) has emerged as a potential non-fossil fuel source to yield transportation fuel via Fischer Tropsch Synthesis (FTS) reaction. Thus, the present study demonstrates the conversion of CO2 containing syngas into fuel range hydrocarbon via Fischer Tropsch Synthesis over Fe–Co bimetallic catalyst. The experimental tests were carried out in a fixed bed continuous reactor to investigate the effect of CO2 on CO/CO2 conversion. Accordingly, obtained data were validated by FTS kinetic model for a plug flow reactor. It was found that the unique combination of Fe and Co bimetallic catalyst facilitates both FTS and water gas shift (WGS) reaction simultaneously that helps to convert CO2 along with CO. It was also observed that the presence of iron in the catalyst helps in conversion of CO2 into hydrocarbons, only when a particular concentration of CO2 in syngas is reached, i.e., critical ratio RC (CO2 /CO + CO2 ) due to the occurrence of reverse water gas reaction (RWGS) which varies with the temperature and the feed gas composition (H2 /CO/CO2 molar ratio). At 240 °C and hydrogen deficient condition, the critical ratio was measured to be 0.74 whereas for hydrogen balanced condition, it was measured 0.6. The kinetic model developed in the present study predicted trends for % CO conversion, % carbon conversion, and % CO2 conversion which is applicable for a wide range of critical ratio RC (CO2 /(CO + CO2 ) = 0 to 1). The model also predicted that a positive conversion of CO2 could be achieved at lower CO2 concentration by increasing the reaction temperature. At 260 °C and 280 °C, the value of Rc were 0.31 and 0.18 were measured. Highlights: CO2 rich syngas could be utilized to produce higher hydrocarbons using Fe–Co catalyst. CO2 conversion essentially starts above a certain concentration called critical ratio. Experimental data directly correlates with simulated data from the developed kinetic model.